Modeling and Optimization of Increasing Teacher Creativity Based on Local Wisdom and Organizational Support - Mohammad Lutfi Nugraha; Soewarto Hardhienata; Rais Hidayat (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
The creativity of Early Childhood Education (PAUD) teachers plays a crucial role in improving the quality of learning, as children require innovative, engaging, and developmentally appropriate stimuli. However, many PAUD teachers still face obstacles in developing creativity due to limited organizational support, reward systems, and the low integration of local wisdom values into the learning process. The purpose of this study is to develop a model for PAUD teacher creativity based on local wisdom and organizational support. The POP-SDM (Modeling and Optimization of Resource Management) method was used in this study. Data collection in the simple qualitative research phase employed direct interviews, recorded and stored via WhatsApp voice notes. In this study, data were also collected using a questionnaire. Model and hypothesis testing were conducted using partial least squares structural equation modeling (PLS-SEM) with the SmartPLS version 3.0 application. The results indicate that improving PAUD teacher creativity in Tasikmalaya City can be achieved through a research constellation model identified through field exploration, supported by strategies derived from SEM analysis and improvement measures based on SITOREM analysis. The research findings confirm that the optimal solution for improving teacher creativity lies in prioritizing indicators that need improvement. Directly, teamwork and organizational climate were shown to have a significant positive effect on teacher creativity, while trust and personality showed little effect. However, indirectly, trust provided a significant positive effect through organizational climate, while teamwork and personality remained insignificant through this pathway.